Identification of exoS, exoU genes in Pseudomonas aeruginosa - Firouzi-Dalvand, Leila; Pooladi, Mehdi (Archives of Advances in Biosciences, 2014)
The bacterium Pseudomonas aeruginosa is a common cause of infections, and infection with antibiotic-resistant strains can be dangerous. The aim of the present study is to investigate the presence of the exoS and exoU genes and the formation of biofilms in clinically isolated P.aeruginosa strains. A total of 126 samples were isolated, and P.aeruginosa was identified using biochemical tests. Bacterial genomic DNA was extracted, and the presence of the exoS and exoU genes were detected by PCR. Biofilms were formed by culturing P.aeruginosaon glass slides in rich medium. The exoU (76%) exoS (68%) genes were detected in of strains isolated from burn (burns caused by heat) patients, respectively. Among the 113 strains isolated from patients with burn infections. An improved understanding of virulence genes and biofilm formation in P.aeruginosa may facilitate the future development of novel vaccines and drug treatments.